The Concentration of Heavy Metals Pb, Cr, and Hg in Body of Water and Sediment, and their relationship with Plankton, Benthos, and Fish Diversity in the Ciliwung River - Khoe Susanto Kusumahadi (Journal of Tropical Biodiversity, 2021)
The objective of this research was to know the concentration of Pb, Cr, and Hg in the body of water and sediment, and their influence on Plankton, Benthos, and Fish diversity in The Ciliwung River. In the downstream of Ciliwung River, there were only Hg and Pb were detected in the water, while in the upstream of Ciliwung River, there were no heavy metals detected. In the rainy season, Hg and Pb were not detected in the body of water. The whole of heavy metals observed was found in the sediment of the Ciliwung River. The concentration of Pb, Cr, and Hg in sediment were significantly different at the location (P<0.05), while according to the replication only Hg was significantly different (P<0.05). The relationship between Hg concentration in River sediment with Hg concentration in water was very significant (P<0.01). The correlation test on the relationship between Hg concentration in water with Plankton and Fish diversity was not significant (P>0.05), while with Benthos Diversity, it was very significant (P<0.01). The correlation test on the relationship between heavy metals concentration in River sediment with Plankton, Benthos, and Fish Diversity showed that the relationship which found significant (P<0.05) was only between Hg concentration in sediment with Benthos Diversity, and the relationship which very significant (P<0.01) was only between Pb concentration in sediment with Benthos Diversity.